Five, six, seven, Nate! - Federle, Tim (Simon & Schuster Books for Young Readers, 2018)
Now on Broadway as second understudy for E.T., Nate Foster keeps in close contact with his best friend, Libby, as he faces his nemesis, Jordan Rylance, and his own insecurities as the cast member with the least training and experience.